The Role of Digitalization in Enhancing the Business Performance of Micro, Small, and Medium Enterprises in Makassar City - Muhammad Difky Al Qadri; Syarifuddin Syarifuddin; Ismail Rasulong (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study examines the role of digitalization in improving the business performance of micro, small, and medium enterprises (MSMEs) in Makassar City, Indonesia. Specifically, it analyzes the effects of digital marketing, e-commerce usage, and digital payment adoption on sales growth, operational efficiency, and market expansion. The research employed a quantitative cross-sectional survey design using purposive sampling, involving 110 MSME owners and managers who had adopted at least one digital tool. Data were analyzed using multiple linear regression. The results indicate that all three digitalization variables significantly and positively influence MSME performance. The regression model demonstrates strong explanatory power, with an R² value of 0.568, meaning that 56.8 percent of the variance in business performance is explained by the digitalization variables. Among the predictors, digital marketing shows the strongest effect, followed by e-commerce usage and digital payment systems. These findings highlight the central role of digital marketing in enhancing visibility, customer engagement, and competitive positioning in urban markets. Despite these positive effects, several barriers constrain the full realization of digital benefits, including low digital literacy, limited internet infrastructure, and high promotional costs. These challenges suggest that digital transformation requires not only technology adoption but also ecosystem support. Practically, the study recommends targeted digital literacy training, improved infrastructure investment, and financial incentives to reduce promotional costs and support sustainable MSME digital transformation in urban Indonesia.